2006
DOI: 10.1210/en.2006-0168
|View full text |Cite
|
Sign up to set email alerts
|

Pigment Epithelium-Derived Factor Is Estrogen Sensitive and Inhibits the Growth of Human Ovarian Cancer and Ovarian Surface Epithelial Cells

Abstract: Epithelial ovarian carcinoma is the most lethal gynecological cancer. However, little is known about the molecular mechanisms underlying the disease development and progression. In this study, we found that the expression of pigment epithelium-derived factor (PEDF) was greatly reduced in ovarian tumors and in ovarian cancer cell lines when compared with their normal precursor, ovarian surface epithelium (OSE). In addition, we showed that exogenous PEDF inhibited the growth of cultured human OSE as well as ovar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
65
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(67 citation statements)
references
References 37 publications
(32 reference statements)
2
65
0
Order By: Relevance
“…17 To date, a few studies have tested the therapeutic potential of PEDF against a number of tumor models, both in vitro and in vivo, and have demonstrated inhibition of growth and the suppression of metastasis in cancers, such as pancreatic carcinoma, 18 prostate carcinoma, 19 melanoma, 20 neuroblastoma 21 and ovarian cancer. 22 In these studies, however, all have used models that have developed following ectopic implantation of cancer cell lines. Hence, no paper has reported the role and antitumor effect of PEDF in an orthotopic model of cancer (i.e., a tumor grown within its organ of origin).…”
Section: Introductionmentioning
confidence: 99%
“…17 To date, a few studies have tested the therapeutic potential of PEDF against a number of tumor models, both in vitro and in vivo, and have demonstrated inhibition of growth and the suppression of metastasis in cancers, such as pancreatic carcinoma, 18 prostate carcinoma, 19 melanoma, 20 neuroblastoma 21 and ovarian cancer. 22 In these studies, however, all have used models that have developed following ectopic implantation of cancer cell lines. Hence, no paper has reported the role and antitumor effect of PEDF in an orthotopic model of cancer (i.e., a tumor grown within its organ of origin).…”
Section: Introductionmentioning
confidence: 99%
“…33 Cheung and colleagues in 2006 found that ER is an important upstream regulator of PEDF in human ovarian cancer and ovarian surface epithelial cells. 34 They found that E2 reduced PEDF levels, and that this process could be prevented by the total ER antagonist, ICI 182,780.…”
mentioning
confidence: 99%
“…PEDF has been shown to have a potential function to inhibit cancer, including osteosarcoma, ovarian carcinoma and prostate cancer (18)(19)(20). Our previous study showed that high levels of PEDF expression in lung cancer tissue were correlated with patients prognosis and that PEDF was an important factor in lung cancer development (14).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that this link to prognosis is the result of increased angiogenesis in the tumour due to the loss of anti-angiogenic control by PEDF. However, it has been recently shown that when engineered to express PEDF, certain cancer cells, such as prostate cancer, osteosarcoma, ovarian cancer, pancreatic cancer, malignant glioma, neuroblastoma, have a reduced growth rate, thus arguing for a potential direct effect of PEDF on cancer cells (15)(16)(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%